Comparison of pain during heel prick in preterm neonates receiving only expressed breast milk and expressed breast milk with kangaroo mother care - Joshi, Gurudutt; Singhvi, Manila (International Journal of Contemporary Pediatrics, 2024)
Background: Newborns’ heels are sampled for blood, which is crucial in the identification of genetic and metabolic illnesses. Repeated painful stimulation impairs the future development of their normal motor and cognitive functions. Hence it is necessary to find out suitable remedy to alleviate the pain. The aim of this study was to observe the premature newborns’ response to pain (Heel prick) by giving either single (EBM) or combined (EBM and KMC). Methods: The analytical cross-sectional study was conducted in NICU of SMIMER. hospital, Surat from March 2022 to February 2023. The study included 56 premature newborns, divided into three groups. Group A received only EBM, Group B received EBM and KMC (15 minutes), and Group C received EBM and KMC (30 minutes) before the heal prick. The pain was assessed by PIPP score in all three groups at the end of 30,60 and 120 seconds after the procedure. Data were analyzed using SPSS 24 and a one-way ANOVA test was applied. Results: The PIPP score after 60 seconds between Group A with B and A with C was statistically significant (p<0.05) whereas Group B with C was insignificant (p>0.05). The score after 60 seconds between Group A with B and A with C was statistically significant (p<0.05) whereas Group B with C was insignificant (p>0.05). Conclusions: EBM with KMC (15 minutes) duration had an effective impact on pain relief as compared to EBM with KMC (30 minutes) duration at the interval of 60 seconds.